Patterns and management of chronic obstructive pulmonary disease in urban and rural China: a community-based survey of 25 000 adults across 10 regions. Issue 1 (19th February 2018) - Kurmi, Om P; Davis, Kourtney J; Hubert Lam, Kin Bong; Guo, Yu; Vaucher, Julien; Bennett, Derrick; Wang, Jenny; Bian, Zheng; Du, Huaidong; Li, Liming; Clarke, Robert; Chen, Zhengming
Abstract : Introduction: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death worldwide, with COPD deaths in China accounting for one-third of all such deaths. However, there is limited available evidence on the management of COPD in China. Methods: A random sample of 25 011 participants in the China Kadoorie Biobank, aged 38–87 years, from 10 regions in China was surveyed in 2013–2014. Data were collected using interviewer-administered questionnaires on the diagnosis ('doctor-diagnosed' or 'symptoms-based') and management of COPD (including use of medication and other healthcare resources), awareness of diagnosis and severity of symptoms in COPD cases. Results: Overall, 6.3% of the study population were identified as COPD cases (doctor-diagnosed cases: 4.8% and symptom-based cases: 2.4%). The proportion having COPD was higher in men than in women (7.9% vs 5.3%) and varied by about threefold (3.7%–10.0%) across the 10 regions. Among those with COPD, 54% sought medical advice during the last 12 months, but <10% reported having received treatment for COPD. The rates of hospitalisation for COPD, use of oxygen therapy at home and influenza or pneumococcal vaccinations in the previous year were 15%, 3% and 4%, respectively. Of those with COPD, half had moderate or severe respiratory symptoms, and over 80% had limited understanding of their disease and need for treatment. Conclusion: Despite a high prevalence of COPD in China and its substantial impact on activities of daily living, knowledge about COPD and its management were limited.